2015
DOI: 10.1097/fbp.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

The nucleus accumbens shell and the dorsolateral striatum mediate the reinforcing effects of cocaine through a serial connection

Abstract: The reinforcing and addictive properties of cocaine are thought to rely on the dopaminergic innervation of the striatum. The ventromedial [i.e. nucleus accumbens shell (NAcc) shell] and dorsolateral [dorsolateral striatum (DLS)] regions of the striatum are serially connected, and it is thought that slowly developing neuroadaptations are responsible for the recruitment of the DLS in mediating habitual drug use after extended drug experience. Remarkably, we have recently shown that the DLS is also involved in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
(84 reference statements)
1
4
0
Order By: Relevance
“…Our demonstration of an increase in the number of pERK1/ 2-positive cells in the striatum of C57Bl/6N mice following acute nicotine as compared to saline administration is consistent with previous reports that showed acute nicotine-induced increases in ERK1/2 in the striatum using an identical dose of nicotine (Valjent et al, 2004;Valjent et al, 2005). Furthermore, although our focus here was on striatal regions, due to the fact that both the ventral and dorsal striatum have been demonstrated to play a role in the rewarding/reinforcing properties of drugs of abuse, including nicotine (Pascual et al, 2009;Veeneman et al, 2012;Veeneman et al, 2015), acute nicotine has also previously been demonstrated to increase pERK1/2 in several other brain areas that are important for Frontiers in Pharmacology frontiersin.org drug-mediated neuroadaptations and consequent drug-seeking responses, such as the PFC, central nucleus of the amygdala, and bed nucleus of the stria terminalis (Valjent et al, 2004;Koob and Volkow, 2010). RasGRF2 WT mice demonstrated an acute nicotine-induced increase in pERK1/2 in the ventral striatum, consistent with our findings above and previous reports (Valjent et al, 2004;Valjent et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Our demonstration of an increase in the number of pERK1/ 2-positive cells in the striatum of C57Bl/6N mice following acute nicotine as compared to saline administration is consistent with previous reports that showed acute nicotine-induced increases in ERK1/2 in the striatum using an identical dose of nicotine (Valjent et al, 2004;Valjent et al, 2005). Furthermore, although our focus here was on striatal regions, due to the fact that both the ventral and dorsal striatum have been demonstrated to play a role in the rewarding/reinforcing properties of drugs of abuse, including nicotine (Pascual et al, 2009;Veeneman et al, 2012;Veeneman et al, 2015), acute nicotine has also previously been demonstrated to increase pERK1/2 in several other brain areas that are important for Frontiers in Pharmacology frontiersin.org drug-mediated neuroadaptations and consequent drug-seeking responses, such as the PFC, central nucleus of the amygdala, and bed nucleus of the stria terminalis (Valjent et al, 2004;Koob and Volkow, 2010). RasGRF2 WT mice demonstrated an acute nicotine-induced increase in pERK1/2 in the ventral striatum, consistent with our findings above and previous reports (Valjent et al, 2004;Valjent et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…For example, the magnitude of the dopaminergic response to self-administered cocaine in drug-naive rats was shown to be similar in the NAc and DS (D'Souza and Duvauchelle, 2006). In addition, Veeneman et al (2012) demonstrated that the DA receptor antagonist ␣-flupenthixol administered into the dorsolateral striatum altered cocaine SA in rats, even after limited exposure (see also Kantak et al, 2002), and disconnection studies between the NAc shell and dorsolateral striatum with ␣-flupenthixol demonstrated that these serial connections mediate cocaine reinforcement during early cocaine exposure (Veeneman et al, 2015). A role for the DS in cocaine reinforcement is consistent with our molecular results above, in which cocaine SA increased pERK activation in the DS in addition to the VS, effects impaired in KO mice.…”
Section: Discussionmentioning
confidence: 92%
“…Considering that different roles for the NAcc shell and core in alcohol reinforcement have been reported (see above), we hypothesized that alpha‐flupenthixol infusions into the NAcc would alter responding for alcohol in a subregion and reinforcement schedule‐dependent manner. With respect to the DLS, recent studies have shown that dopaminergic signalling in this brain region might, alongside its role in drug‐seeking habits, also be involved in the reinforcing properties of cocaine (Veeneman et al ., , ; Willuhn et al ., ). Therefore, we hypothesized that dopamine receptor blockade in the DLS would affect alcohol self‐administration under both FR and PR schedules of reinforcement.…”
Section: Introductionmentioning
confidence: 99%